Marketing Management: Present, Past and Future in the Modern Business Scene - Joshua, Leonard (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Marketing management has undergone substantial transformation in response to economic development, technological innovation, globalization, and evolving consumer behavior. Initially rooted in production efficiency and transactional exchanges, marketing management has progressively evolved into a strategic, customer-centric, and value-driven organizational function. In the contemporary business environment, marketing management integrates digital technologies, data analytics, relationship marketing, and sustainability principles to create competitive advantage and long-term value for both firms and stakeholders. This paper aims to provide a comprehensive and systematic analysis of marketing management from three temporal perspectives: the past, the present, and the future. The historical analysis explores the evolution of marketing orientations, ranging from production and sales orientation to market, societal, and relationship-oriented marketing. The discussion of the present focuses on marketing management practices within modern business environments characterized by digitalization, global competition, empowered consumers, and rapid innovation. Furthermore, this paper examines future trends in marketing management, including artificial intelligence, big data analytics, sustainability-driven marketing, experience-based marketing, and agile marketing practices. By adopting an integrative literature-based approach, this study contributes to a deeper understanding of how marketing management has transformed into a strategic discipline essential for organizational survival and growth. The findings suggest that organizations capable of aligning historical insights, contemporary practices, and future-oriented strategies will be better positioned to achieve sustainable competitive advantage in an increasingly complex and dynamic marketplace.